Level of awareness of smart manufacturing technologies and its nexus to adoption among micro, small, and medium enterprises in the Philippines - Barroga, Kenneth D.; Wabina, Vanessa Ellen R.; Sales, Anthony C. (Philippine journal of science)
"With the rapid developments in the manufacturing industry, micro, small, and medium enterprises (MSMEs) need to equip with smart manufacturing (SM) technologies to keep abreast with the fourth industrial revolution (FIRe). this paper sought to assess the level of SM awareness among MSMEs in the Philippines and its correlation to technology uptake. The data were obtained from the survey gathered from 496 cooperators of the Department of Science and Technology's (DOST) Small Enterprises Technology Program (SETUP), a government initiative that assists MSMEs in upgrading technologies. This study employed mixed methods of quantitative [principal component analysis (PCA), index construction, and Pearson's r test] and qualitative [triangulation method using key informant interviews (KII)] analyses to provide an understanding of the variations of awareness and adoption of nine SM-enabling technologies" - title page.